Pengembangan Literacy Digital Anak Usia Dini Melalui Pembelajaran Computer Kids - Shofa, Mila Faila (Early Childhood Research Journal (ECRJ), 2023)
The purpose of this study is to determine the developing digital literacy in early childhood through Computer Kids learning. This research uses descriptive qualitative methods. Data collection techniques through interviews, documentation, and observation. Data validity techniques use source triangulation and triangulation methods. Data analysis uses interactive data analysis, presentation of data, data reduction, and drawing conclusions. The results showed that Computer Kids learning at PAUD Inclusion Saymara was carried out once a week in the multimedia room. Before carrying out learning, educators make plans related to the material to be delivered. The learning materials for Computer kids include getting to know the hardware, the parts of the computer, turning the computer on and off. In addition, software that is suitable for early childhood is also introduced such as interactive games, Microsoft Paint, Microsoft Word where children can recognize shapes, letters, and numbers. Through this Computer Kids learning, children have the knowledge and skills to utilize digital media wisely, intelligently, meticulously, and precisely according to their age development.